Chagas' disease: pathology of chronic lesions - Andrade, Zilton A- (Revista de Patologia Tropical / Journal of Tropical Pathology, 2011)
The morphologic features of the indeterminate and the chronic cardiac forms of Chagas' disease, and their clinicai correlations, are briefly reviewed. The significance of mild focal myocarditis as the main change of the indeterminate form, the myocardial inflammation and flbrosis of the chronic cardiac form, pius the mvolvement of the conductíng system, are particularly considered.